Experimental performance of circular concrete-filled steel tubular members with inner profiled steel under lateral shear load. (15th December 2019) - Shi, Yan-Li; Xian, Wei; Wang, Wen-Da; Li, Hua-Wei
Highlights: Very limited study on the shear performance of CFST members with inner profiled steel is available. The shear performance is experimentally investigated. The effects of shear-span ratio and profiled steel ratio on the shear capacity are studied. A formula is proposed for predicting the shear capacity Abstract: This paper experimentally investigated the shear performance of circular concrete-filled steel tubular (CFST) members with inner profiled steel under lateral shear load. Twenty specimens with inner I or cruciform section profiled steel were tested. Different parameters including shear-span ratio ( m  = 0.3, 0.4, 0.6, 0.8 and 1.0) and profiled steel ratio ( α ss  = 0.028, 0.031, 0.057 and 0.062) were compared and discussed. Failure modes, shear load versus deflection curves, load-strain curves, ductility and shear capacity of the specimens were investigated. The test results showed that the CFST members with inner profiled steel exhibited good ductility under lateral shear load and the extension of cracks in core concrete can be restrained or delayed owing to the inserted profiled steel. The specimens with diverse shear-span ratios showed various failure modes, i.e., shear failure mode and flexure failure mode. With the increase of m, failure modes changed from shear dominated to flexure dominated failure and shear capacity decreased significantly due to the changing of load transfer mechanism. Moreover, inserted profiled steel had an effect on ductility and shear capacity because of the increasing cross-section area of profiled steel and the composite action between profiled steel and concrete. A simplified formula for predicting shear capacity was proposed and predicted results were generally good agreement with experimental results.